Gandhi & Churchill : the epic rivalry that destroyed an empire and forged our age - Herman, Arthur, 1956- (Bantam Books, 2008)
A dual portrait of Winston Churchill and Mahatma Gandhi describes their fierce, forty-year struggle against each other for the future of Indian independence, from the outbreak of the Great War to the end of World War II, detailing their dramatic influence on each other, as well as their lasting legacy for the British empire and the future course of modern history.